Effect of Celery Extract Administration on 8-OHdG and Number of Foam Cell in Wistar Strain Rats With A High-Fat Diet - Budiarto, Agnes; Nasihun, Taufiqurrachman; Hussaana, Atina (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2017)
BACKGROUND: A high fat diet, accompanied by high frequency eating, results in hyperlipidemia. One prevention for hyperlipidemia is administration of celery extract.OBJECTIVE: to explore the effect of celery extract on the level of 8-OHdG (8 -Hydroxy-2’-Deoxy Guanosine) and the number of foam cell.METHODS: Experimental studies with post-test only control group design used Wistar rats, administered with adrenaline and high-fat diet forhyperlipidemic induction.Total of 35 rats were divided into 5 groups: negative controls (Neg-G); positive control treated with simvastatin (Nor-G); ES25-G,ES50-G, and ES75-G group were treated with 25 mg/200 g BW, 50 mg/200 g BW, and 75 mg/200 g BW celery extract, respectively. The treatment was given for 30 days. The 8-OHdG level was determined by ELISA, whereas the number of foam cells was determined by histopathologic preparations with HE staining. Data analysis was conducted by Kruskal-Wallis and Mann-Whitney.RESULTS: Mann-Whitney analysis showed levels of 8-OHdG in ES-25-G 12.13±0.21, ES-50-G 7.23±0.25, ES-75-G 4.41±0.45 significantly lowerthan the Nor-G 14.30±0.66, respectively p<0.001. The number of foam cells in the ES-25-G was 7.57±0.53, ES-50-G 6.57±0.79, ES-75-G 3.43±0.53,significantly lower than the Neg-G 13.57±1.27, respectively p<0.001.CONCLUSION: Celery extract capable of decreasing levels of 8-OHdG and the number of foam cells in Wistar rats induced with adrenaline and high-fatdiet.